Particle dynamics around a Schwarzschild modified black hole - Husanboy Hoshimov (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
In this work, we study the dynamics of test particles around a modified Schwarzschild black hole, taking into account the effects of the Generalized Uncertainty Principle (GUP). Using a metric that incorporates GUP corrections, we derive analytical expressions for the Keplerian (orbital), radial, and vertical epicyclic oscillation frequencies of particles orbiting the black hole. The analysis reveals that as the GUP correction parameter increases, the Keplerian and vertical oscillation frequencies decrease, whereas the radial oscillation frequency increases. These results indicate that GUP effects have a significant impact on particle trajectories around black holes and could, in principle, be detected through astrophysical observations such as quasi-periodic oscillations (QPOs).